Portaria PRR5 nº 135, de 25 de julho de 2019 - Marcelo Alves Dias de Souza (DOU, Brasília, DF, 26 jul. 2019, Seção 2, p. 58., 2019)
Dispensa e designação de servidores para o exercício de função comissionada.